Study of lymphnode lesions by fine needle aspiration cytology and histopathology: A study of 125 cases - Dr. Dipeeka Patel; Dr. Ragini Patel (Tropical Journal of Pathology and Microbiology, 2019)
Background: Fine needle aspiration cytology (FNAC) is a simple and rapid diagnostic technique and because of early availability of results, simplicity, minimal trauma and complication, the aspiration cytology is now considered as a valuable diagnostic aid and is gaining popularity. It also helps in giving proper direction for appropriate investigations. Objectives: To find out number of cases where FNAC of the lymph nodes picked up an unsuspected malignancy and to correlate the cytological findings with the histopathological findings in cases where lymph node biopsy is done. Methodology: It was a prospective study done on patient who presented with lymphadenopathy to various departments and referred to pathology department. The aspirate was collected from the enlarged lymphnodes using standard procedure with proper aseptic condition. The aspirate was examined for the amount and nature of the aspirated material, and then several smears were prepared. Smears were immediately fixed in 95% ethyl alcohol, and these smears were examined using various stains like haematoxylin and eosin stain, PAS stain also MGG’s stain and Ziehl Neelsen stain. Observations: out of total 125 patients, 91 (73.60%) were Male patients and 34 (26.40%) were Female patients with M:F ratio of 2.79:1 with Male predominance. Distributions of all lymph node lesions shows cervical site i.e. 97 (77.6%) followed by inguinal i.e. 14 (11.2%) and other sites. Among all lymphnode lesions, 66.40% were neoplastic lesions and 33.60% were non- neoplastic lesions. Neoplastic lesions were more common in cervical group and Metastatic squamous cell carcinoma was more common in cervical group. Cytological diagnosis was correlated with histopathology diagnosis in 13.6% cases. Conclusion: FNAC can help not only to differentiate among lymphoma, and metastasis, but also to identify nonspecific reactive lymphadenitis and specific infections such as tuberculosis lymphadenitis. The results are quite encouraging and even more advanced diagnostic tools available, FNAC can still recommended as the initial diagnostic test in the evaluation of superficial lymphadenopathy.